1994
DOI: 10.1002/ccd.1810310406
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of pulmonary artery pressure from pulmonary vein wedge pressure

Abstract: Correlations between pulmonary artery and pulmonary vein wedge pressures were investigated in 13 patients with atrial septal defect and 1 patient with Tetralogy of Fallot. Pulmonary vein wedge pressure wave form resembled that of pulmonary artery pressure, and the former lagged behind the latter by 70 to 110 msec (mean 88 +/- 14) as observed by the fluid-filled catheter system. Diastolic pulmonary artery and diastolic pulmonary vein wedge pressures were nearly identical. Although systolic and mean pulmonary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Although it is important to accurately assess PAP, passage of a catheter across a small shunt increases risk in an already vulnerable patient population. Prior analyses in patients with nonshunt‐dependent PBF suggest that PVWP would underestimate directly measured PAP [5, 6, 8, 9, 13]. We found the opposite and suggest that this systematic difference reflects the fact that passage of a catheter across a relatively small shunt can significantly impede PBF resulting in a falsely lowered estimation of PAP.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although it is important to accurately assess PAP, passage of a catheter across a small shunt increases risk in an already vulnerable patient population. Prior analyses in patients with nonshunt‐dependent PBF suggest that PVWP would underestimate directly measured PAP [5, 6, 8, 9, 13]. We found the opposite and suggest that this systematic difference reflects the fact that passage of a catheter across a relatively small shunt can significantly impede PBF resulting in a falsely lowered estimation of PAP.…”
Section: Discussionmentioning
confidence: 57%
“…This technique is relatively straight forward when an atrial communication is present. The accuracy of PVWP has been validated in other patient populations, including patients with congenital heart disease but nonshunt‐dependent PBF [5–9]. In these studies, PVWP correlates closely with PAP at lower mean pressures, but tends to underestimate PAP at higher mean pressures [5, 6, 8].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation was poor in patients with normal PAP, but good in patients with pulmonary hypertension. Recently, Chern et al [5] have demonstrated in patients with atrial septal defect (n ϭ 13) and tetralogy of Fallot (n ϭ 1) that the systolic and the mean PAP correlated well with PVWP; however, there were discrepancies when the systolic and the mean PAP exceeded 35 and 20 mm Hg.…”
Section: Discussion Previous Studymentioning
confidence: 94%
“…When the pulmonary artery is not entered in the patients with complex congenital heart disease, a pulmonary venous wedge pressure (PVWP) is recorded to be taken as the PAP. Although PVWP usually reflects PAP when the PVWP is within normal limit [1][2][3][4][5], there is little published data on the applicability and feasibility of PVWP in assessing Fontan candidates with low pulmonary blood flow and pulmonary blood pressure [6]. The purpose of this study is to investigate the relationship between PVWP and PAP in various congenital heart disease, including complex heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…When the pulmonary artery is not entered in the patients with complex congenital heart disease, a pulmonary venous wedge pressure (PVWP) is recorded to be taken as the PAP. Although PVWP usually reflects PAP when the PVWP is within normal limit [1–5], there is little published data on the applicability and feasibility of PVWP in assessing Fontan candidates with low pulmonary blood flow and pulmonary blood pressure [6]. The purpose of this study is to investigate the relationship between PVWP and PAP in various congenital heart disease, including complex heart disease.…”
Section: Introductionmentioning
confidence: 99%